Edad y crecimiento de Cheirodon interruptus (Characiformes: tetragonopteridae) en la cuenca alta del río Sauce Grande, provincia de Buenos Aires - López Cazorla, Andrea C. (2006)
The objective of the present work was to determine the age that reaches Cheirodon interruptus (Jenyns, 1842) in the Sauce Grande river basin, and to estimate its growth parameters. Sampling was performed seasonally by electrofishing, in three sites along the main river. A total of 164 individuals were caught, and total length (TL, mm) and weight (W, g) were recorded. The age was determined over a sub-sample of 154 fish, by means of scale reading. The growth parameters of von Bertalanffy’s equation were estimated using Least Squares method. Fish size ranged between 29 - 62 mm, with a mean of 44.73 mm (± 7.46). Mean TL by season was 38.17 mm (± 5.47) in summer, 43.25 mm (± 9.00) in autumn, 45.00 mm (± 5.10) in winter and 47.73 mm (± 6.45) in spring. Length-weight relationship for the total population was W = 6 x 10 -5 TL 2.61 (R 2 = 0.88). One annulus formation occurred yearly, at the end of autumn, assigning one year to each mark. Three age classes were determined (0 – 2), being age 0 the most abundant (84 %). The growth parameters for the total population were : L∞ = 57.63 mm; k = 0.69 y t 0 = -1.72.